Blocking ethylene perception enhances flooding tolerance in rice seedlings - Ella, Evangelina S.; Kawano, Naoyoshi; Yamauchi, Yasuo; Tanaka, Kiyoshi; Ismail, Abdelbagi M. (Commonwealth Scientific and Industrial Research Organisation, 2003)
Large areas of rainfed lowlands in South and Southeast Asia annually experience short durations of flash flooding during the rice-growing season, which dramatically affect plant survival and productivity. Submergence-intolerant cultivars usually show progressive leaf chlorosis, which could be triggered by ethylene produced during submergence. An ethylene inhibitor, 1-methyl cyclopropene (MCP), was used to evaluate the effect of ethylene on chlorophyll degradation and plant survival. Seedlings of two cultivars, FR13A (tolerant) and IR42 (intolerant) either untreated or treated with MCP for 5 h before submergence, were submerged for 6 d. Chlorophyll content and activity and gene expression of chlorophyllase, the first enzyme involved in chlorophyll degradation, were determined during submergence and recovery, and survival scores were recorded after 21 d of recovery. MCP treatment decreased chlorophyll degradation, lowered the activity and gene expression of chlorophyllase, and improved seedling survival in IR42, but with no effect on underwater relative shoot expansion. Chlorophyllase enzyme activity and gene expression were lower in FR13A, suggesting that this cultivar might have reduced ethylene level or sensitivity. Manipulation of ethylene synthesis or sensitivity through molecular approaches might therefore help improve tolerance of flash flooding in rice.